2015
DOI: 10.1074/jbc.m114.626697
|View full text |Cite
|
Sign up to set email alerts
|

Non-germ Line Restoration of Genomic Imprinting for a Small Subset of Imprinted Genes in Ubiquitin-like PHD and RING Finger Domain-Containing 1 (Uhrf1) Null Mouse Embryonic Stem Cells

Abstract: Background: Once erased, DNA methylation in imprinted genes was shown previously to be re-established only through germ line passage. Results: UHRF1 re-expression in Uhrf1Ϫ/Ϫ mouse embryonic stem (ES) cells restores DNA methylation for a few imprinted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…During the course of writing, a paper from the Wong group investigating the behaviour of UHRF1 rescue cells found that a number of imprinted genes showed gains in methylation in that system too [55]. Methylation gain was only seen at some of the imprinted loci, and there was no clear link to the location of the gDMR, the presence of antisense transcripts or the type of imprint.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of writing, a paper from the Wong group investigating the behaviour of UHRF1 rescue cells found that a number of imprinted genes showed gains in methylation in that system too [55]. Methylation gain was only seen at some of the imprinted loci, and there was no clear link to the location of the gDMR, the presence of antisense transcripts or the type of imprint.…”
Section: Discussionmentioning
confidence: 99%
“…UHRF1 specifically binds to hemimethylated DNA via its SRA domain [120][121][122][123] and recognizes the N-terminal tails of histone H3 di-and tri-methylated at lysine 9 (H3K9me2/me3) via combined binding of its tandem Tudor domain (TTD) and its plant homeodomain (PHD) [124][125][126][127] . These specific chromatin interactions of UHRF1 are necessary for the recruitment of DNMT1 to replicating chromatin and DNA methylation maintenance, since mutations preventing histone binding in any of the domains abolished DNA methylation by DNMT1 in cells 125,127,128 . In addition to its role in targeting of DNMT1, UHRF1 was also shown to stimulate the catalytic activity of DNMT1 through direct interaction 129,130 .…”
Section: Recruitment Of Dnmt1 To Replicating Chromatinmentioning
confidence: 99%
“…Despite intense work in the DNA methylation field, its role in regulating differentially expressed genes is controversial (Gutierrez-Arcelus et al, 2013). Many studies in organisms across the evolutionary spectrum have demonstrated that DNA methylation does not serve as a universal mechanism of repressing gene expression (Feng et al, 2010;Grow et al, 2015;Gutierrez-Arcelus et al, 2013;Jackson-Grusby et al, 2001;Jacob et al, 2015;Potok et al, 2013;Qi et al, 2015;Zemach et al, 2010;Zhang et al, 2016). In fact, most data indicate that relatively few genes are induced when methylation is lost: there is a lack of global gene induction in mammalian cells deficient in the proteins required for DNA methylation, namely ubiquitin-like with PHD and ring finger domains 1 (Uhrf1) (Qi et al, 2015) or DNA methyltransferase 1 (DNMT1) (Jackson-Grusby et al, 2001), or during the stage of early embryogenesis when the parental methylome is nearly completely erased (Grow et al, 2015;Potok et al, 2013).…”
Section: Introductionmentioning
confidence: 99%